2022
DOI: 10.1007/s10585-022-10183-6
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiotherapy of nodal oligometastases from prostate cancer: a prisma-compliant systematic review

Abstract: Androgen deprivation therapy (ADT) is the standard treatment of metastatic prostate cancer (PCa). However, metastases-directed therapies can delay the initiation or switch of systemic treatments and allow local control (LC) and prolonged progression-free survival (PFS), particularly in patients with lymph nodes (LN) oligometastases. We performed a systematic review on stereotactic body radiotherapy (SBRT) in this setting. Papers reporting LC and/or PFS were selected. Data on ADT-free survival, overall survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 58 publications
6
8
0
Order By: Relevance
“…The review also reported generally low rates of acute toxicity after SBRT. Specifically, acute and late G1-G2 toxicity rates were about 1.9% and on average severe acute and late toxicities ≥G3 occurred in about 0.6% of cases (12). This date is in line with our prospective series in which no acute and late toxicity episodes occurred.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The review also reported generally low rates of acute toxicity after SBRT. Specifically, acute and late G1-G2 toxicity rates were about 1.9% and on average severe acute and late toxicities ≥G3 occurred in about 0.6% of cases (12). This date is in line with our prospective series in which no acute and late toxicity episodes occurred.…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, the present is the largest prospective study of 1.5T lymphnode SBRT on MR-linac in patients with PCa. Previous evidence, mainly retrospective on the use of SBRT in the PCa lymphnode oligometastases with conventional linacs reported local control rates around 93% at two years (10)(11)(12). In our experience, in line with these previous experiences, the 2-year local control rate was 94.5%.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Additionally, local therapy can potentially benefit patients with oligometastatic disease, as well. A recent systematic review by Zamagni et al evaluating the potential benefit of SBRT in patients with nodal oligometastatic disease secondary to prostate cancer, for example, found that SBRT was safe, offered high rates of local control, and allowed for a delay in the initiation of androgen deprivation therapy [ 14 ]. Given the potential mechanistic differences in oligoprogression in patients on ICIs, local therapy may be of particular benefit to this patient population.…”
Section: Introductionmentioning
confidence: 99%